(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to build an educational program to develop the skills of preparing theatrical texts based on folk tales for students of the Institute of Fine Arts in school theater, and then measure the size of the effect in developing the skills of preparing texts. The experimental approach and the experimental design with the experimental group and the control group, with the application of a pre and post test, where the research sample consisted of (30) male and female students from the theater department at the Institute of Fine Arts, second stage / Karkh The researcher has prepared two tools for the current research: First: a cognitive test consisting of two questions Second: a skill test (note form) Among the most important results that resulted from The impact size of the program. The effect size of the program in the post- skill performance test was (0,21), and therefore the effect size is considered to have a high impact for the experimental group. Direct inquiry: 1. Determine the exact path. The clear increase in the number of theatrical texts for the same experimental group gives a clear indication of the effectiveness of the educational program. Effective: -1. The inclusion of topics and special parameters previous texts of the authority and the School of Fine Arts, the school theater course The possibility of benefiting from the educational program prepared to develop the skills of preparing theatrical texts for students in teaching some practical skills in general An educational program to develop the skills of preparing theater scenarios based on folk tales for students of the Institute of Fine Arts in school theater